2008
DOI: 10.1016/j.jhep.2008.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Massive hepatic angiomyolipoma in a young woman with tuberous sclerosis complex: Significant clinical improvement during tamoxifen treatment

Abstract: This is to our knowledge the first report in which tamoxifen has been successfully used in a TSC patient with multiple liver angiomyolipomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 23 publications
1
8
0
1
Order By: Relevance
“…It has been reported only in 6–10% of cases 4. In the literature, only few cases of symptomatic hepatic angiomyolipomas like in our observation have been reported 2 5. This hepatic involvement can be revealed as in our case by abdominal pain, distension and hepatomegaly 2…”
Section: Discussionsupporting
confidence: 63%
“…It has been reported only in 6–10% of cases 4. In the literature, only few cases of symptomatic hepatic angiomyolipomas like in our observation have been reported 2 5. This hepatic involvement can be revealed as in our case by abdominal pain, distension and hepatomegaly 2…”
Section: Discussionsupporting
confidence: 63%
“…It is encouraging to note that there is limited case report evidence that treatment of TSC related tumors with tamoxifen may also correlate with findings in mouse models. There is one report of a massive liver angiomyolipoma in a 26 year old female with TSC2 disease that regressed after treatment with tamoxifen [73]. The MEK1/2 inhibitor was used to treat estrogen induced tumors derived from Tsc2 -null uterine leiomyoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Most hepatic AML occurs in females, so the relationship between hepatic AML and fertility must be considered, particularly in childbearing age women. Although Yeh et al reported that estrogen and progesterone receptors were negative in all 12 female patients with hepatic AML by immunohistochemical study [25], tamoxifen (a widely used drug in humans for the prevention and the treatment of estrogen-related cancer) has been successfully used in the treatment of hepatic AML recently [26]. Therefore, the role of sex hormones in the pathogenesis and growth of hepatic AML is still uncertain.…”
Section: Discussionmentioning
confidence: 99%